Academic life in shade and light: Snapshots of well-being - Berecz, Réka (Central European Journal of Educational Research, 2026)
Bibliography of the reviewed book: Pusztai, G., & Kovács, K. (Eds.) (2026). Well-Being of Academic Staff in Rapidly Changing Higher Education. A Focus on Central and Eastern Europe. Peter Lang Verlang.